2020
DOI: 10.1590/1984-0462/2020/38/2018158
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinemia Type Iii: A Case Report of Siblings and Literature Review

Abstract: ABSTRACT Objective: Tyrosinemia type III (HT III) is the rarest form of tyrosinemia, and the full clinical spectrum of this disorder is still unknown. The neurological involvement varies, including intellectual impairment and attention deficit disorder with hyperactivity (ADHD). We report the case of two siblings diagnosed with HT III at different ages. Case description: The index case was diagnosed by newborn screening for endocrine and metabolic disorders, starting a low-protein diet immediately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In their study involving 13 patients, Ellaway et al [2001] showed that 75% of patients with tyrosinemia type III had neurological manifestations, which included intellectual disability, ataxia, increased deep tendon reflexes, tremors, microcephaly, dyslexia, attention deficit, ataxia, hypotonia, and seizures. Attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder in these patients have been previously reported in the literature [Tahiroğlu et al, 2008;Barroso et al, 2020]. We planned to follow-up our patient for autism spectrum disorder because she had stereotypical movements and made less eye contact compared to peers.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In their study involving 13 patients, Ellaway et al [2001] showed that 75% of patients with tyrosinemia type III had neurological manifestations, which included intellectual disability, ataxia, increased deep tendon reflexes, tremors, microcephaly, dyslexia, attention deficit, ataxia, hypotonia, and seizures. Attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder in these patients have been previously reported in the literature [Tahiroğlu et al, 2008;Barroso et al, 2020]. We planned to follow-up our patient for autism spectrum disorder because she had stereotypical movements and made less eye contact compared to peers.…”
Section: Discussionmentioning
confidence: 85%
“…A summary of all previously reported patients with biallelic HPD mutations is presented in Table 2 [Cerone et al, 1997;Standing et al, 1998;Rüetschi et al, 2000;Tomoeda et al, 2000;Heylen et al, 2012;Szymanska et al, 2015;Coskun et al, 2016;Barroso et al, 2020]. Of these patients, 4 were diagnosed by neonatal screening, and diet was initiated in all of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A metabolic deficiency of tyrosine aminotransferase ( Figure 1 ), Richner-Hanhart syndrome leads to a marked tyrosinaemia which can result in corneal opacities if the dietary intake of phenylalanine and tyrosine is not restricted [ 7 ]. A small number of cases of HPPD deficiency have been reported [ 8 , 9 ] called tyrosinaemia type III ( Figure 1 ). Tyrosinaemia Type 1 is where fumarylacetoacetase, the last enzyme in the pathway is deficient resulting in acute tissue injury with children usually dying in the first two years of life.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…15,16 This theory is further supported by the fact that HT3, the disease caused by a deficiency in the same enzyme that NTBC blocks, also presents with neurological manifestations including developmental delay. [17][18][19][20] Complications attributed to NTBC treatment other than low IQ include attention deficits, memory and processing problems, psychomotor and behavioral issues, and impairment of executive function and social cognition. [21][22][23][24][25][26][27][28] To date, the only therapeutic option for patients refractory to NTBC or with disease progression despite NTBC therapy, and the only curative treatment for HT1, is liver transplantation.…”
Section: Introductionmentioning
confidence: 99%